2011
DOI: 10.1021/ml200030q
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of INCB3284, a Potent, Selective, and Orally Bioavailable hCCR2 Antagonist

Abstract: b S Supporting Information M acrophages, which are derived from monocytes, a subset of leukocytes, are well-characterized mediators of tissue destruction. These cells can be activated to secrete proinflammatory cytokines such as TNFR and IL-1β, tissue-degrading enzymes such as MMPs, and other chemokines that mediate the influx of other inflammatory cells. 1 Excessive recruitment of these cells to sites of inflammation leads to significant tissue destruction and contributes to the morbidity of chronic inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 12 publications
1
29
1
Order By: Relevance
“…43,44 Consequently, targeting chemokines with inhibitors, antibodies, and antagonists as new options in the treatment of patients with arthritis was promising. The development of antagonists of CCR1, 44,45 CCR2, 46,47 and CCR5 48 presented promising results in different murine models of arthritis, but the antagonists failed during clinical trials. Many reasons can be found to explain the failure in the development of these drugs, such as inappropriate target selection in some cases, insufficient dosing of chemokine receptor antagonists in vivo, 49 and problems related to properties and complexity of the chemokine system, including redundancy and pleiotropy.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Consequently, targeting chemokines with inhibitors, antibodies, and antagonists as new options in the treatment of patients with arthritis was promising. The development of antagonists of CCR1, 44,45 CCR2, 46,47 and CCR5 48 presented promising results in different murine models of arthritis, but the antagonists failed during clinical trials. Many reasons can be found to explain the failure in the development of these drugs, such as inappropriate target selection in some cases, insufficient dosing of chemokine receptor antagonists in vivo, 49 and problems related to properties and complexity of the chemokine system, including redundancy and pleiotropy.…”
Section: Discussionmentioning
confidence: 99%
“…The CCR2 antagonist failed to show any significant improvement compared with placebo for any of the end points studied (Horuk, 2009). Incyte (Wilmington, DE) has disclosed a number of CCR2 antagonists, including INCB3284, which was one of their clinical compounds in phase II clinical studies for multiple sclerosis and lupus (Xue et al, 2011). No data from the clinical trials were ever reported.…”
Section: B CC Chemokine Receptorsmentioning
confidence: 99%
“…Although the structure of these antagonist is different from each other but still all of them share the same binding pocket onto CCR5 receptor with differential binding mode [28]. INCB 3284 dimesylate, BMS CCR2 22, JNJ 27141491, RS 504393, Teijin compound 1, RS 102895 hydrochloride, are selective CCR2 antagonist (Figure 1), where INCB 3284 dimesylate and JNJ 27141491 are orally bio available for their potency [29][30][31][32][33]. Gamma amino butyric acid (Table 1) is a potent inhibitor for SDF1 and it is explored well for its efficacy for inhibition of migration of CD133+ haematopoietic stem cells and progenitor cells but the same will be effective for HIV1 treatment or not is not explored well.…”
Section: Ccr2 Ccr5 and Sdf1 Antagonistic In Hiv1 Therapeuticsmentioning
confidence: 99%